Cartilage regeneration in zebrafish depends on Nrg1/ErbB signaling pathway - Sapède, Dora; Bahraoui, Sarah; Abou Nassif, Léa; Barthelaix, Audrey; Mathieu, Marc; Jorgensen, Christian; Djouad, Farida (Frontiers in Cell and Developmental Biology, 2023)
Objective: Cartilage, as the majority of adult mammalian tissues, has limited regeneration capacity. Cartilage degradation consecutive to joint injury or aging then leads to irreversible joint damage and diseases. In contrast, several vertebrate species such as the zebrafish have the remarkable capacity to spontaneously regenerate skeletal structures after severe injuries. The objective of our study was to test the regenerative capacity of Meckel’s cartilage (MC) upon mechanical injury in zebrafish and to identify the mechanisms underlying this process. Methods and Results: Cartilage regenerative capacity in zebrafish larvae was investigated after mechanical injuries of the lower jaw MC in TgBAC(col2a1a:mCherry), to visualize the loss and recovery of cartilage. Confocal analysis revealed the formation of new chondrocytes and complete regeneration of MC at 14 days post-injury (dpi) via chondrocyte cell cycle re-entry and proliferation of pre-existing MC chondrocytes near the wound. Through expression analyses, we showed an increase of nrg1 expression in the regenerating lower jaw, which also expresses Nrg1 receptors, ErbB3 and ErbB2. Pharmacological inhibition of the ErbB pathway and specific knockdown of Nrg1 affected MC regeneration indicating the pivotal role of this pathway for cartilage regeneration. Finally, addition of exogenous NRG1 in an in vitro model of osteoarthritic (OA)-like chondrocytes induced by IL1β suggests that Nrg1/ErbB pathway is functional in mammalian chondrocytes and alleviates the increased expression of catabolic markers characteristic of OA-like chondrocytes. Conclusion: Our results show that the Nrg1/ErbB pathway is required for spontaneous cartilage regeneration in zebrafish and is of interest to design new therapeutic approaches to promote cartilage regeneration in mammals.